Forecasting social and economic development of Sevastopol and long-term analysis - E. A. Matushevskaya (Plekhanov Russian University of Economics, 2021)
The efficiency of state governance can be attained only on the basis of developing new systems of informational-analytical support, through which it could be possible to reach completeness and accuracy of information and to make and implement managerial decisions at all level of state power. The article studies mechanism of informational-analytical support of forecasting social and economic development of the city of Sevastopol’. On the basis of empiric research methods and approaches to forecasting social and economic development of Sevastopol’ were identified and a medium-term forecast of social parameters was made. The authors presented the forecast of the index of gross regional product on the basis of correlation – regressive analysis. To forecast social and economic development of Sevastopol’ the following factors were used: the number and structure of labour at the age of 15 +; dynamics of work volume carried out in ‘Construction’; index of investment into fixed capital. This approach can be useful for bodies of state power and introduction of the forecasting model can help settle problems dealing with optimizing state and managerial decision-making on the regional level.